Analisis High Oil Temperature pada Auxiliary Power Unit Pesawat Terbang - . Jamaludin (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
The Auxiliary Power Unit on Airbus aircraft will keep the aircraft comfortable both in the air and on the ground, so customers feel happy. High oil temperature at the Auxiliary Power Unit is a loss and will be dangerous if repair is not done immediately. The contributing factors are: 1) Blockage in the air intake duct or inlate duck; 2) blockages in the ducting oil cooler, ECB electronic control box (59KD), oil temperature sensor (8092KM), oil cooler (8079KM), cooling fan assembly (8053KM) and APU generator (8XS); and 3) oil quality degradation. Preventive maintenance methods that can be carried out so that high oil temperatures do not occur in the Auxiliary Power Unit (APU), such as: 1) always maintaining the quantity and quality of the APU oil, namely by always checking the oil on time and according to the checking schedule; 2) change the APU oil filter according to schedule; and 3) always keep the APU cooling ducts / ducts clean from dust or other contamination, so that the APU oil cooling system can maintain the APU oil temperature always below 162.780C (3250F).